2011
DOI: 10.1021/tx2001515
|View full text |Cite
|
Sign up to set email alerts
|

Application of CYP102A1M11H as a Tool for the Generation of Protein Adducts of Reactive Drug Metabolites

Abstract: Covalent binding of reactive metabolites (RMs) to proteins is considered to be one of the important mechanisms by which drugs can cause tissue damage. To facilitate the study of drug-protein adducts, we developed a potentially generic method for producing high levels of covalently modified proteins. A highly active drug metabolizing P450 BM3 mutant (CYP102A1M11H) is used for drug bioactivation. Because of its His-tag, CYP102A1M11H is easily removed by nickel affinity chromatography, facilitating subsequent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 53 publications
(146 reference statements)
5
40
3
Order By: Relevance
“…Electrochemistry can generate large amounts of RMs without biological crude matrices, however, it cannot mimic all CYPs-mediated metabolic reactions due to the lack of interactions between enzymes and substrates [20,21]. In addition, some studies have reported the characterization of drug-protein adducts using the bioengineered mutant cytochrome P450 BM3 (CYP102A1) system coupled with MS analysis [12,13]. CYP102A1 mutants appeared to produce high levels of human relevant RMs of several drugs [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Electrochemistry can generate large amounts of RMs without biological crude matrices, however, it cannot mimic all CYPs-mediated metabolic reactions due to the lack of interactions between enzymes and substrates [20,21]. In addition, some studies have reported the characterization of drug-protein adducts using the bioengineered mutant cytochrome P450 BM3 (CYP102A1) system coupled with MS analysis [12,13]. CYP102A1 mutants appeared to produce high levels of human relevant RMs of several drugs [22].…”
Section: Discussionmentioning
confidence: 99%
“…CYP102A1 mutants appeared to produce high levels of human relevant RMs of several drugs [22]. However, in the case of other drugs, the CYP102A1 mutant system might be less useful or non-relevant RMs might be generated [13]. Since HLMs are a predictive in vitro system for human drug bioactivation, it is valuable to use HLMs as a bioactivation system for the method to generate and characterize drug-protein adducts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] Recently, the first mass spectrometric analysis of DF-protein adducts reported modification of the single free cysteine residue in β-lactoglobulin upon electrochemical oxidation of DF. 24 CYP102A1M11H has been shown previously to produce high levels of human-relevant RMs of several drugs, including DF, 4'-OH-DF and 5-OH-DF. 10,23 In the present study, a recently developed method is used to characterize the P450dependent covalent protein modification by DF metabolites by mass spectrometry of tryptic digests and by using purified CYP102A1M11H as bioactivation system.…”
Section: Introductionmentioning
confidence: 99%